Children's Experiences on Learning the 21st-Century Skills With Digital Games. Issue 6 (25th April 2019) - Kahila, Juho; Valtonen, Teemu; Tedre, Matti; Mäkitalo, Kati; Saarikoski, Olli
Previous research on learning-related digital games has focused on studying learning outcomes with mostly adult participants. This study explores what children have experienced they have learned by playing digital games, how these learning experiences relate to 21st-century skills, and in which contexts do the children benefit from playing digital games. The data were collected from children's essays, which were analyzed using qualitative content analysis. Results reveal that children's learning experiences are often related to 21st-century core subjects and skills, but they also reported improved physical abilities and sports competences from digital games. Children felt that the skills they had gained were beneficial in the contexts of school, sports, and friendships. The results contribute to our understanding of digital games and children by providing children's perspective on digital games and learning.